2017
DOI: 10.5430/ijhe.v6n1p217
|View full text |Cite
|
Sign up to set email alerts
|

Feel, think, teach – Emotional Underpinnings of Approaches to Teaching in Higher Education

Abstract: The paper investigates relations between higher education teachers' approaches to teaching and their emotions during teaching, as well as their emotion regulation strategies. Based on the assumption that the approaches hinge on emotional experiences with higher education teaching and learning, three studies assessed teachers' emotions, their emotion regulation strategies and their approaches to teaching with questionnaires. Study 1, with n = 145 German university teachers and teaching assistants, found relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…What they do and how they do it can help transfer these practices to other faculty members and contagion them from their good work. Previous studies also concluded this [27,15]. Thus, university faculty should bear in mind that it is not only the content of their lessons that is important, but that they should also pay attention to how they teach, in a twofold sense, since while there can be no doubt that methodologies impact learning, it is no less certain that the climate generated and the way in which faculty and students interact are also vital elements in this process.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…What they do and how they do it can help transfer these practices to other faculty members and contagion them from their good work. Previous studies also concluded this [27,15]. Thus, university faculty should bear in mind that it is not only the content of their lessons that is important, but that they should also pay attention to how they teach, in a twofold sense, since while there can be no doubt that methodologies impact learning, it is no less certain that the climate generated and the way in which faculty and students interact are also vital elements in this process.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…Emotions are a key part of learning. Faculty members should therefore take them into account and strive to emotionally connect to students [27, 28]. Quinlan [15] claims that emotions are a vital aspect of relationships, arguing that the way we feel with and about others is fundamental to the quality of the relationships we establish.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding solely quantitative studies, positive teaching emotions (e.g., pride) have been positively associated with student-focused teaching, while negative emotions (e.g., anxiety) have been positively associated with teacher-focused teaching ( Trigwell, 2012 ; see Kordts-Freudinger, 2017 for similar results concerning positive affect). Positive emotions such as joy have also been found to be positively correlated with personal and professional balance, control, value, and perceived success in teaching in early-career faculty, while for negative emotions such as anxiety, the opposite has been documented ( Stupnisky et al, 2019b ).…”
Section: Introductionmentioning
confidence: 91%
“…Author et al, 2018), which is necessary for learneroriented education (e.g. Kordts-Freudinger, 2017). It can be conceptualized as a situated response (e.g.…”
Section: Discussionmentioning
confidence: 99%